Risk factors for Carbapenem-resistant Acinetobacter baumannii contamination on hospital surfaces: a multi-year environmental monitoring study in Shanghai, China - Zhang, Xing; Tian, Liang; Wu, Jiaying; Chen, Taiyao; Shi, Tingting; Ge, Yilin; Zhu, Renyi; Chen, Jian (Frontiers in Microbiology, 2025)
BackgroundCarbapenem-resistant Acinetobacter baumannii (CRAB) poses a significant threat to human health in hospital settings. These environments could serve as a reservoir for CRAB, since Acinetobacter baumannii (AB) exhibits strong survival capabilities outside the human body. Therefore, it is necessary to investigate the distribution of CRAB in the environment and identify the risk factors associated with its positive detection rate.MethodsFrom 2018 to 2023, long-term environmental monitoring of surfaces around CRAB patients was conducted across 16 hospitals in Shanghai. During each quarter, 48 environmental samples, along with information about the samples, were collected. Bacterial isolates were collected, and antimicrobial susceptibility testing (AST) was performed in accordance with the Clinical and Laboratory Standards Institute (CLSI) guidelines (2019–2021 edition). The CRAB detection rate in the environmental samples was compared across different variables. For nominal categorical variables, intergroup differences were analyzed using Pearson’s chi-squared (χ2) test. In addition, logistic regression analysis was employed to identify risk factors associated with CRAB-positive environmental samples.ResultsA total of 10,268 samples were included in this study, among which 391 tested positive for CRAB. The overall CRAB positivity rate on environmental surfaces was 3.81%. Significant differences in positivity rates were observed across hospital levels, departments, sampling locations, and exposure frequencies (p < 0.05). Compared to Class B secondary hospitals, the following hospital classes showed significantly higher risks of CRAB detection: Class A secondary hospitals (OR = 13.34, 95%CI: 3.25–54.79, p < 0.001), Class B tertiary hospitals (OR = 20.63, 95%CI: 5.10–83.49, p < 0.001), and Class A tertiary hospitals (OR = 8.77, 95%CI: 2.14–35.87, p = 0.003). Compared to internal medicine departments, environmental surfaces in the following high-risk departments demonstrated higher rates of CRAB detection: surgical departments (OR = 1.93, 95%CI: 1.23–3.05, p = 0.005) and intensive care units (ICUs) (OR = 3.10, 95%CI: 2.19–4.39, p < 0.001). Additionally, surfaces located inside wards (OR = 1.834, 95%CI: 1.230 ~ 2.736, p = 0.003) and those with high-touch frequency (OR = 1.467, 95%CI: 1.134 ~ 1.898, p = 0.003) were identified as risk factors for the positive detection rate of CRAB in the environment.ConclusionClass A secondary hospitals and Class B tertiary hospitals should prioritize infection control measures to prevent the dissemination of CRAB. Special attention should be given to high-risk areas, such as the surgical department and ICU, with enhanced disinfection of high-touch surfaces within patient wards.